2013
DOI: 10.1016/j.apcatb.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation by solar photo-Fenton in pet bottles of wild enteric bacteria of natural well water: Absence of re-growth after one week of subsequent storage

Abstract: a b s t r a c tIron photo-assisted inactivation of wild enteric bacteria (total coliforms/E. coli and Salmonella spp.) was carried out in water from the Sahelian wells having different pH (W1: 4.9 and W2: 6.3) and a natural iron content of 0.07 mg/L. We evaluate the efficiency of the disinfection on different systems containing both or only one /hv led to total inactivation of Salmonella and E. coli. The natural iron content (0.07 mg/L) was enough to drive an efficient photo-Fenton process leading to total bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…However, the remaining H 2 O 2 amount (3-4 mg/L) in the treated water disappears completely from the water after 2 or 3 days of storage. This H 2 O 2 depletion was also reported in our previous paper (Ndounla et al 2013). …”
Section: Solar Radiation Systemsupporting
confidence: 59%
See 1 more Smart Citation
“…However, the remaining H 2 O 2 amount (3-4 mg/L) in the treated water disappears completely from the water after 2 or 3 days of storage. This H 2 O 2 depletion was also reported in our previous paper (Ndounla et al 2013). …”
Section: Solar Radiation Systemsupporting
confidence: 59%
“…The photo-Fenton process was firstly more efficiently been used under acidic conditions (pH 2.5-3) for biorecalcitrant chemical compound degradation (Herrera et al 1998;Sarria et al 2005;Kenfack et al 2009;Malato et al 2009). After the first records of the efficiency of photoFenton disinfection at near-neutral pH (Rincon and Pulgarin 2006), several authors have conducted investigations to evaluate it in natural water and some at neutral pH (Moncayo-Lasso et al 2009;Sciacca et al 2010;Ndounla et al 2013). The photochemical reduction of nitrite or nitrate and the chemical oxidation of ammonia could lead to OH • radical generation (Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…At the low intensity experiments, some distinct phases can be observed. First of all, the bacterial population does not decrease until 180 min of continuous illumination, presenting an initial shoulder, as it was proposed by many works [7,10,13]. In addition, in the pre-mentioned works, this shoulder was not (or was mildly) accompanied by an increase in bacterial population.…”
Section: Resultsmentioning
confidence: 66%
“…However, the coincidence of ample solar supplies in these areas favored studies on solar purification of drinking water sources [3][4][5]. A fair share of SODIS works, reviewed by McGuigan et al [6] have demonstrated the ability of UVA and UVB wavelengths of the solar spectrum to inactivate a vast number of microorganisms, such as Escherichia coli, Salmonella, Shigella Flexneri, Fusarium and more [7][8][9][10]. Slowly, the interest has moved to wastewater treatment, and photolytic and photocatalytic methods have been used to target the present microorganisms [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that the presence of some salts causes a baro-protective effect on the cells [40] and samples with higher contents of soluble solids would require higher sonication times. Apart from the physical damage, during the ultrasound treatment of the sample, there is ample generation of reactive oxygen species ( Å OH radicals [41], singlet oxygen [42,43]), as mentioned before, which are known to stress bacteria and lead to cell death [25,44].…”
Section: Results Of the Step-wise Construction Of The Joint Treatmentmentioning
confidence: 99%